After Columbus : the horse's return to America - Viola, Herman J.; Howland, Deborah (Norwalk, Conn. : Soundprints, 1992)
Discusses the reintroduction of the horse by Columbus, after its having been extinct in North America for 8500 years, and how that animal changed forever the lives of North Americans.
7 - 9 years
Keywords: Columbus, Christopher; Horses -- Juvenile literature. -- America; Indians of North America -- Domestic animals; Horses